Factors associated with the utilization of antenatal care services in rural areas of Assam, India - Kakati, Rana; Barua, Kabita; Borah, Madhur (International Journal Of Community Medicine And Public Health, 2016)
Background: Utilization of antenatal care services is very essential for reducing maternal mortality in a country like India which is experiencing high maternal mortality especially in the state of Assam being at the top position. Almost 90% of the maternal deaths can be prevented by timely medical interventions. However, adequate utilization of antenatal care (ANC) services is far away from WHO recommendations. The objective is to assess the utilization of antenatal care services and also to determine the underlying factors influencing the utilization of antenatal care services in rural areas of Assam. Methods: A cross sectional study was conducted from September-December 2015. Eight villages were selected randomly and sample size was calculated as 300.All currently married women having children of less than one year of age comprised of study population. Results: Out of 300 women all were registered during antenatal period and among them 53% were registered during first trimester. Among them 68.7% women had more than three antenatal visits, 90% were immunized with TT and 71.6% had consumed 100 or more IFA tablets. The utilization of antenatal care services were found to be significantly associated with the age of the women , religion, caste, socioeconomic class, place of delivery, mode of delivery, parity (P<0.05). Conclusions: The present study revealed that factors like age, religion, caste, socioeconomic status, place of delivery, parity were associated with utilization of antenatal care services. Government should make effort to increase the level of awareness and knowledge among the women about the adequate utilization of antenatal care services.